Antioxidant activities of polysaccharides from Hyriopsis cumingii - Qiao, Deliang; Ke, Chunling; Hu, Bing; Luo, Jianguang; Ye, Hong; Sun, Yi; Yan, Xiaoyan; Zeng, Xiaoxiong (Carbohydrate polymers, 2009)
The antioxidant activities of crude Hyriopsis cumingii polysaccharides (HCPS) were evaluated both in vitro and in vivo. In vitro antioxidant assay, HCPS (crude and its purified fraction) could scavenge hydrogen peroxide, free radicals of superoxide anion and 2,2-diphenyl-1-picryl-hydrazyl, chelate ferrous ion and reduce ferric ion. Except for metal ion chelating activity, HCPS-3 exhibited much higher antioxidant activities than crude HCPS, HCPS-1 and HCPS-2. For antioxidant testing in vivo, different doses of crude HCPS were orally administrated over a period of 15 days in a d-galactose induced aged mice model. As results, administration of crude HCPS inhibited significantly the formation of malondialdehyde in mice livers and serums and raised the activities of antioxidant enzymes and total antioxidant capacity in a dose-dependent manner. The results suggested that HCPS had direct and potent antioxidant activities.